2017
DOI: 10.1002/cjas.1439
|View full text |Cite
|
Sign up to set email alerts
|

Is it safe to bring myself to work? Understanding LGBTQ experiences of workplace dignity

Abstract: Despite increased efforts by more organizations to be seen as "gay-friendly," workplaces remain challenging sites for LGBTQ employees to navigate. We examine the ways in which LGBTQ employees experience dignity threats in the workplace and the protection strategies they use to deflect those threats. Interviews with 36 LGBTQ working adults revealed that their dignity is threatened by a range of identitysensitive inequalities that undermine their safety and security when they claim authentic gendered/sexual iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 42 publications
(74 reference statements)
0
39
0
2
Order By: Relevance
“…For instance, Sayer () asserted that one's experience of dignity relies upon ‘words and deeds’, as respectful communication recognizes another person as ‘someone who is more than what they do for a living, who demands respect simply as a person’ (p. 572; see also Bolton, ; Hodson, ). Additionally, numerous empirical studies noted violations of human dignity that arose from rude or disrespectful interaction (e.g., Apostolidis, ; Baker, ; Cleaveland, ). The current study extends this original thinking by revealing that communication is not limited to meeting desires for respectful interaction associated with inherent dignity, but instead plays an equally prominent role in the earned and remediated components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Sayer () asserted that one's experience of dignity relies upon ‘words and deeds’, as respectful communication recognizes another person as ‘someone who is more than what they do for a living, who demands respect simply as a person’ (p. 572; see also Bolton, ; Hodson, ). Additionally, numerous empirical studies noted violations of human dignity that arose from rude or disrespectful interaction (e.g., Apostolidis, ; Baker, ; Cleaveland, ). The current study extends this original thinking by revealing that communication is not limited to meeting desires for respectful interaction associated with inherent dignity, but instead plays an equally prominent role in the earned and remediated components.…”
Section: Discussionmentioning
confidence: 99%
“…Another response to dignity threats is engaging in resistance, such as absenteeism, labour organizing, striking, sabotage, and quitting (Cleaveland, ; Hodson, ; Roscigno and Hodson, ; Stuesse, ). Resistance to indignity also has been shown to be: subtle, such as cynicism communicated by employees rejecting offensive organizational cultures (Fleming, ); productive, such as advocacy and organizing efforts by LGBTQ employees experiencing dignity threats due to sexual orientation and/or gender expression (Baker, ); and creative, such as the myriad tactics captured in a collection of organizational misbehaviour narratives (e.g., wearing ugly ties to resist a company dress code; Karlsson, ).…”
Section: Workplace Dignitymentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of research to date has been conducted with ethnographic methods, which has revealed rich and nuanced accounts of problematic workplaces, employee vulnerabilities, and responses to dignity threats ranging from identity work and coping to resistance and retaliation. For example, researchers have studied the abuse and humiliation of nurses (Khademi, Mohammadi, & Vanaki, 2012), the social and career harms inflicted on lesbian, gay, bisexual, transgender, and queer (LGBTQ) employees (Baker & Lucas, 2017), the stigmatization of custodians (Rabelo, 2017), the undervalued occupational status of child care workers (Nelson & Lewis, 2016), the economic insecurity of day laborers (Purser, 2009), the objectification of fashion models (Mears & Finlay, 2005), and the dehumanization of professional athletes (Dufur & Feinberg, 2007), to name only some. On one hand, this ethnographic approach is a strength as it points to the multitude of ways dignity can be threatened in the workplace.…”
mentioning
confidence: 99%
“…Research undertaken on workplace dignity thus far has primarily relied on ethnographic methods, exploring, for example: the lived experience of nurses facing dignity violations (Khademi et al, 2012), discursive analyses of neoliberal discourse of dirty work (Purser, 2009), and the protection strategies that minority groups use when facing workplace dignity violations (Baker & Lucas, 2017). These idiographic approaches demonstrate the breadth of manifestations of workplace dignity.…”
Section: Introductionmentioning
confidence: 99%